2020
DOI: 10.1002/hyp.13875
|View full text |Cite
|
Sign up to set email alerts
|

Predicting evaporation from mountain streams

Abstract: Evaporation can be an important control on stream temperature, particularly in summer when it acts to limit daily maximum stream temperature. Evaporation from streams is usually modelled with the use of a wind function that includes empirically derived coefficients. A small number of studies derived wind functions for individual streams; the fitted parameters varied substantially among sites. In this study, stream evaporation and above-stream meteorological conditions (at 0.5 and 1.5 m above the water surface)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 76 publications
(126 reference statements)
1
12
0
Order By: Relevance
“…Therefore, the Penman coefficients appear to have a reasonable amount of empirical support for application to streams. Szeitz and Moore (2020) found that the Brady et al. (1969) equation performed almost as well as the Penman wind function.…”
Section: Experience From the Literaturementioning
confidence: 94%
See 4 more Smart Citations
“…Therefore, the Penman coefficients appear to have a reasonable amount of empirical support for application to streams. Szeitz and Moore (2020) found that the Brady et al. (1969) equation performed almost as well as the Penman wind function.…”
Section: Experience From the Literaturementioning
confidence: 94%
“…(1969) wind functions with apparently reasonable results (Garner et al., 2014; King & Neilson, 2019; Leach & Moore, 2011; Magnusson et al., 2012). The Penman coefficients were based on empirical data over a range of “wet” surfaces (Penman, 1948, 1956), and Szeitz and Moore (2020) found that they predicted Q e with an uncertainty of ± 14 W normalm 2 (±20% of the mean flux) compared to measurements using in‐stream pans at nine sites in southwest British Columbia. Therefore, the Penman coefficients appear to have a reasonable amount of empirical support for application to streams.…”
Section: Experience From the Literaturementioning
confidence: 99%
See 3 more Smart Citations